2009
DOI: 10.1002/stem.20080600
|View full text |Cite
|
Sign up to set email alerts
|

Development of human nervous tissue upon differentiation of embryonic stem cells in three-dimensional culture

Abstract: Researches on neural differentiation using embryonic stem cells (ESC) require analysis of neurogenesis in conditions mimicking physiological cellular interactions as closely as possible. In this study, we report an air-liquid interface-based culture of human ESC. This culture system allows three-dimensional cell expansion and neural differentiation in the absence of added growth factors. Over a 3-month period, a macroscopically visible, compact tissue developed. Histological coloration revealed a dense neural-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
29
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
8
1
1

Relationship

2
8

Authors

Journals

citations
Cited by 43 publications
(29 citation statements)
references
References 40 publications
0
29
0
Order By: Relevance
“…The alternative to presynthesized scaffolds is the generation of an extracellular matrix by the cells themselves in 3D tissue culture. Previous studies from our laboratory have shown that this is basically possible [13,14].…”
mentioning
confidence: 78%
“…The alternative to presynthesized scaffolds is the generation of an extracellular matrix by the cells themselves in 3D tissue culture. Previous studies from our laboratory have shown that this is basically possible [13,14].…”
mentioning
confidence: 78%
“…Thanks to induced PSC technology (Takahashi and Yamanaka 2006), the ethnic diversity of humans can be included into the analysis through a careful selection of PSC lines (Fakunle and Loring 2012). Three-dimensional culture techniques (Hoelting et al 2013) have enabled the generation of PSC-derived organoids (e.g., Preynat-Seauve et al 2009), allowing putative toxic compounds to be tested on tissues rather than on isolated cells. Finally, the use of PSCs to generate mice with humanized organs (e.g., Takebe et al 2013) provides new opportunities to represent physiological complexity.…”
mentioning
confidence: 99%
“…recently, a method that allows brain embryonic stem cell expansion has been described using an air-liquid interface-based method. 12 We show here that the use of such an air-liquid interface system to co-cultivate brain cells together with glioblastoma cells recapitulates features of clinical Gbm and offers a unique simple tool to assess the pharmacodynamic properties of potential anticancer drugs.…”
mentioning
confidence: 83%